Complications Associated With Termination of Pregnancy - Khan, Faryal; Zahoor, Farnaz; Khel, Sidra Hassan; Riaz, Aleena (Biological and Clinical Sciences Research Journal, 2025)
Termination of pregnancy is a commonly performed obstetric procedure, but it may be associated with maternal complications, particularly when performed in later gestational ages. Objective: To assess the complications related to the termination of pregnancy. Methods: A cross-sectional study was conducted from 15-September 2024 to 15-March 2025 at the Department of Obstetrics and Gynecology, Lady Reading Hospital, Peshawar. Eighty-eight patients presenting for termination of pregnancy were selected. We observed the complications following the termination procedure. Results: Mean age was 32.59±4.40 years. Complications-wise, bleeding was seen in 19 (21.6%) patients, infection in 12 (13.6%) patients, D&C was repeated in 5 (5.7%) patients, and transfusion was required in 3 (3.4%) patients. Bleeding was notably higher in patients in the second trimester (P = 0.05). Repetition of D&C, infection, and transfusion were higher in patients in the second trimester, but the association was not notable. Conclusion: We conclude that the complications following termination of pregnancy in our study were bleeding followed by infection, repeated D&C, and the need for transfusion. Patients in the second trimester are more likely to develop complications post-procedure of termination.